Optimizing the Method for Differentiation of Macrophages from Human Induced Pluripotent Stem Cells. (3rd March 2022) - Li, Shanshan; Song, Lili; Zhang, Yingwen; Zhan, Zhiyan; Yang, Yi; Yu, Lisha; Zhu, Hua; Huang, Weihua; Wang, Wanqiao; Feng, Haizhong; Li, Yanxin
Abstract : Macrophage is a very promising cell type for cancer immunotherapy, yet it is difficult to obtain enough functional macrophages for clinical cell therapy. Herein, we descibe a reliable method to produce functional macrophages through the differentiation of human induced pluripotent stem cells (hiPSCs). By optimizing the size control of embryoid bodies (EBs), we accelerated the differentiation process of macrophages and increased the production of macrophages without attenuating macrophage functions. Our final yield of macrophages was close to 50-fold of starting iPSCs. The macrophages showed phagocytic capacity in vitro and a xenograft tumor model. M0 macrophages could be further polarized into M1 and M2 subtypes, and M1 cells exhibited typical proinflammatory characteristics. Moreover, we found that hematopoietic differentiation originated from the outside of EB and matured inward gradually. Taken together, our protocol provides an effective method for the generation of macrophages comparable to blood-derived macrophages, which provides potential value for cell therapy and gene editing studies.